Performance Measurement Using Balanced Scorecard For Non-Profit Organization: A Case Report - Muhammad Alif Maulana; Faza Athalah; Irischa Pramesti Anindito (Journal of Economics and Business UBS, 2024)
Every organization has a goal, and a performance management system is required to increase the probability of the organization achieving its goals. As most organizations focus on bottom line measurements and organizational growth, the case is different for nonprofit organizations whose measurement focus is on stakeholder satisfaction and social impact. Nonprofit organizations also have the luxury of not needing to retain remaining unused funds for growth as the unused funds will be returned to donors. The application of performance management systems in nonprofit organizations is still at a minimum. The Balanced Scorecard (BSC) is one of the most well known performance management system tools for corporations. Some perspectives in BSC such as customer may not be appropriate to nonprofit organizations and further modification needs to be done to find the best framework for performance management. This paper aims to develop and propose a performance management system framework in the case study of Common Room Networks Foundation. Common Room is a nonprofit organization based in Bandung, Indonesia, who become agents that bridge the interests of the beneficiaries of the local-based Internet development program. The study will begin with interviews to collect existing organization performance measurements, map the strategic objectives according to perspectives, and determine the Key Performance Indicator (KPI) that best measures the success of the organization. It is hoped that this framework can be applied to any nonprofit organization of any specialization.